2021
DOI: 10.1021/acs.langmuir.0c02715
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Polymer–Particle Interaction in PEO Solutions

Abstract: We have measured the electrophoretic mobility and diffusion coefficient of carboxylate-modified and sulfate-modified polystyrene latex particles in poly(ethylene oxide) aqueous solutions. Carboxylate -modified polystyrene particles have shown a bound polymeric layer as the surface net charge vanishes even at very low poly(ethylene oxide) concentration. The polymeric layer causes a lower electrophoretic mobility and slower Brownian diffusion than that corresponding to the bare particles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The negative zeta potential supports this consideration. Espasa-Valdepeñas et al . showed that PEO adsorbed carboxylate-modified nanoparticles in an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative zeta potential supports this consideration. Espasa-Valdepeñas et al . showed that PEO adsorbed carboxylate-modified nanoparticles in an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The negative zeta potential supports this consideration. Espasa-Valdepenãs et al 44 showed that PEO adsorbed carboxylate-modified nanoparticles in an aqueous solution. Because the main chain of HEUR molecules is PEO, it is consistent that the HEUR molecule binds to MION2.…”
Section: Calibration Curve Of the Local Viscosity Around Mionmentioning
confidence: 99%
“…(1) polyhedral oligomeric silsesquioxanes (POSS) nanoparticles with the diameter d on the order of 1 to 3 nm, 27,40,46 (2) quantum dots (QDs) with 2 nm < d < 10 nm, 36,67 (3) gold nanoparticles with 5 nm < d < 400 nm, 11,12,14,19,34,39,43,49,50,55,56,63,78 (4) magnetic nanoparticles with 5 nm < d < 20 nm, 18,31,37,38,51,52,62,64,70,71,76,80 (5) silica (SiO 2 ) nanoparticles with 5 nm < d < 50 nm, 26,29,30,44,48,57,60,61,74,81 (6) polystyrene nanoparticles with 20 nm < d < 2000 nm, 13,16,17,22,33,35,53,65,66,68,69,72 (7) nanorods with dimensions from (1) nm to (100) nm made of Au, magnetic elements and their dioxides, or titanium dioxide (TiO 2 ). 15,…”
Section: Introductionmentioning
confidence: 99%
“…The development of nanoparticle chemistry in recent years has enabled the synthesis of nanoparticles with well-controlled size, shape, and surface chemistry, yielding a library of nanoparticles available for investigating fundamental scientific problems and exploring nanoparticle-based applications. Nanoparticles commonly used in the studies of nanoparticle dynamics in a polymer matrix include polyhedral oligomeric silsesquioxanes (POSS) nanoparticles with the diameter d on the order of 1 to 3 nm, ,, quantum dots (QDs) with 2 nm < d < 10 nm, , gold nanoparticles with 5 nm < d < 400 nm, ,,,,,,,,,,,, magnetic nanoparticles with 5 nm < d < 20 nm, ,…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, not only the geometry but also the affinity of the polymer for the particle surface can influence the particle velocity. Accordingly, sticky and nonsticky pictures have been explored by simulation, scaling theory, and experiments on Brownian motion. ,, …”
Section: Introductionmentioning
confidence: 99%